A study on factors that influence the performance of bumiputera small and medium enterprises (SME) in Kedah - Muhammad Sufian, Muda (2021)
This study aims at investigating the relationship between business characteristics, business networking, business financing support and strategic planning toward performance of enterprises. Customers who have loan and financing at MARA Kedah which the selected respondents either micro, small and medium enterprises categories and questionnaire has been used as the instrument for data collection which consist a total of 42 items including demographic background of the respondents. The findings revealed there are positive relationships between the business characteristics, business networking, and business financing support toward performance of enterprises. This study demonstrated that business characteristic has the most significant relationship towards performance of enterprises. On the other hand, based on the findings the strategic planning has no significant relationship toward the performance of enterprises. The findings of this study could contribute both to theorists and managerial practitioners.